(untitled) (Heritage, 2020)
Employees are the key in any business because the outcome of a business depends on their achievement. Their importance is multiplied when dealing with business in times of crisis. Under such conditions, some companies make a strategic decision to move towards change and transform their business. In order to achieve the vision, it is necessary, on the one hand, to transform the business from the root, and to change the business culture on the other, align it with new plans, change the way of work and the way of thinking of employees. In this context, it is necessary to include employees in the entire transformation as soon as possible, and the presented case study of Philip Morris Serbia just illustrates this example. By analyzing secondary data, the text considers the significance of the strategic role of HRM, primarily training and development as a means to help employees keep pace with change, lead them and grow within the organization. Particular emphasis is placed on how through a well-conceived and embedded HR strategy with the overall direction of business transformation, turbulent times within the company and beyond can be transformed into an opportunity to create a competitive advantage.